A Burgeoning Community of Justice? The European Union as a Promoter of Transitional Justice. (13th June 2021) - Verovšek, Peter J
Abstract: Emerging as it does from Europe's age of total war, the European Union (EU) has a long-standing interest in promoting transitional justice. However, since this desire to become a community of justice has remained implicit, it has been overlooked by much of the existing literature. Despite internal tensions between East and West, over the last 20 years the EU has sought to actively promote justice both 'down' onto its member states and 'out' into world politics. Based on an analysis of legal texts and regulations, as well as demonstrative case studies, I argue that the EU's record in this area is mixed. Although it has been able to use membership to force changes as part of the accession process, existing member states and states outside of Europe have resisted these efforts. Despite its desire to incorporate transitional justice into its legal regime, I show that the EU's efforts in promoting transitional justice remain largely political.